An assessment of potential causal links between deglaciation and eruption rates at arc volcanoes - Conway, Chris E.; Pure, Leo R.; Ishizuka, Osamu (Frontiers in Earth Science, 2023)
One of the fundamental questions that underpins studies of the interactions between the cryosphere and volcanism is: do causal relationships exist between the ice volume on a volcano and its eruption rate? In particular, it is critical to determine whether the decompression of crustal magma systems via deglaciation has resulted in enhanced eruption rates along volcanic arcs in the middle to high latitudes. Evidence for such a feedback mechanism would indicate that ongoing glacier retreat could lead to future increases in eruptive activity. Archives of eruption frequency, size, and style, which can be used to test whether magma generation and eruption dynamics have been affected by local ice volume fluctuations, exist in the preserved eruptive products of Pleistocene-Holocene volcanoes. For this contribution, we have reviewed time-volume-composition trends for 33 volcanoes and volcanic groups in arc settings affected by glaciation, based on published radiometric ages and erupted volumes and/or compositions of edifice-forming products. Of the 33 volcanic systems examined that have geochronological and volumetric data of sufficient resolution to compare to climatic changes since ~250 ka, increases in apparent eruption rates during post-glacial periods were identified for 4, with unclear trends identified for a further 12. Limitations in the geochronological and eruption volume datasets of the case studies make it difficult to test whether apparent eruption rates are correlated with ice coverage. Major caveats are: (1) the potential for biased preservation and exposure of eruptive materials within certain periods of a volcano’s lifespan; (2) the relative imprecision of geochronological constraints for volcanic products when compared with high-resolution climate proxy records; (3) the reliance on data only from immediately before and after the Last Glacial Termination (~18 ka), which are rarely compared with trends throughout the Pleistocene to test the reproducibility of eruptive patterns; and (4) the lack of consideration that eruption rates and magma compositions may be influenced by mantle and crustal processes that operate independently of glacial advance/retreat. Addressing these limitations will lead to improvements in the fields of geochronology, paleoclimatology, and eruption forecasting, which could make valuable contributions to the endeavours of mitigating future climate change and volcanic hazards.